“Demographic Winter”: Does it Have an Impact on Indonesia? Population Economic Records - Rosyadi Rosyadi; Tri Cicik Wijayanti; Jiuhardi Jiuhardi (Faculty of Economic and Business, 2023)
The originality of this paper focuses on existing material. It has implications for uncovering Indonesia's barriers to population growth, which are associated with economic components such as employment, wages, and happiness. On this basis, the orientation of this study is centered on cycles in the